Knowledge, attitude, and practice of nurses toward COVID-19: A cross-sectional study in a referral hospital of Indonesia - Marthoenis Marthoenis; Maskur Maskur (Wolters Kluwer Medknow Publications, 2021)
Background: Limited study has been conducted on the Indonesian nurses' knowledge, attitude, and behavior toward Coronavirus disease 2019. We investigated the Knowledge, Attitude, Practice (KAP) of nurses working in the referral hospital toward the COVID-19 disease. Materials and Methods: Using a questionnaire on KAP toward COVID-19, a cross-sectional online data collection was conducted in the mid of 2020 to examine the nurses' KAP, perception, and experience toward COVID-19. Results: The correct rate of knowledge was 85.60%. No significant difference of all KAP items between the COVID-19 and regular nurses was observed (P>0.05). They had positive attitudes regarding the pandemic and good practices for virus transmission prevention. Most nurses were worried that they will be infected by COVID-19 (91.53%). Conclusions: The Indonesian nurses have good knowledge, a positive attitude, and good practices regarding the virus, transmission, and prevention. The fact that the majority of nurses feel worried demands further investigations.